2001
DOI: 10.1111/j.1349-7006.2001.tb01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Increase of DNA Copy Number in the 2q24 Chromosomal Region and Its Association with a Poor Clinical Outcome in Hepatoblastoma: Cytogenetic and Comparative Genomic Hybridization Analysis

Abstract: In a cytogenetic and comparative genomic hybridization (CGH) study of 38 hepatoblastomas, we found gain of 1q in 17 tumors (44.7%), that of 2/2q in 14 (36.8%), that of 20/20q in 9 (23.7%) and that of 8/8q in 8 (21.0%), loss of 4q in 4 (10.5%) and no DNA copy changes with normal karyotype or no mitotic cells in 11 (28.9%). Eleven tumors with 2/2q gain detected by CGH had a total chromosome 2 gain, a partial 2q gain, or a total chromosome 2 gain with an augmented partial 2q region; the common region for DNA copy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 18 publications
(23 reference statements)
3
34
0
1
Order By: Relevance
“…To our knowledge, CGH has been used to screen 148 hepatoblastomas for chromosomal gain and loss (Steenman et al, 1999;Gray et al, 2000;Weber et al, 2000;Kumon et al, 2001;Mullarkey et al, 2001;Terracciano et al, 2003). With CGH, most of these 148 tumors showed gains or losses, and in most studies, CGH results confirmed those reported in studies of hepatoblastoma karyotypes, that is, frequent gain of 1q, 2/2q, and 8/8q.…”
Section: Discussionsupporting
confidence: 75%
“…To our knowledge, CGH has been used to screen 148 hepatoblastomas for chromosomal gain and loss (Steenman et al, 1999;Gray et al, 2000;Weber et al, 2000;Kumon et al, 2001;Mullarkey et al, 2001;Terracciano et al, 2003). With CGH, most of these 148 tumors showed gains or losses, and in most studies, CGH results confirmed those reported in studies of hepatoblastoma karyotypes, that is, frequent gain of 1q, 2/2q, and 8/8q.…”
Section: Discussionsupporting
confidence: 75%
“…Frequent gains in chromosome 2q24 were found in hepatoma (Kumon et al, 2001), esophageal carcinoma (Du Plessis et al, 1999), inherited ovarian carcinoma (Tapper et al, 1998) and nasopharyngeal carcinoma (Chien et al, 2001), while losses in 2q24 were reported in basal cell adenocarcinoma of the salivary gland (Toida et al, 2001), colon tumors (Yeatman et al, 1996) and colorectal tumors (Peng et al, 2002). Weak linkage of the 2q24 region in multiple sclerosis of Nordic populations was also observed by microsatellite marker typing (Akesson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The present clinical factors predicting outcome include the level of alpha-feto protein, histology, disease stage and growth pattern of the tumor. [2][3][4] Chromosomal gains of 2q, 8q and 20 and high expression of telomerase or PLK1 were shown to be moleculargenetic markers predicting poor outcome [5][6][7][8] ; however, none have been proven to be independent prognostic factors by multivariate analysis.…”
mentioning
confidence: 99%